On Quantum Possibilistic Paradoxes and Logical Contextuality - Santos, Leonardo Silva Vieira (2021)
In the present master\'s thesis we study logical contextuality and inequality-free proofs of quantum contextuality and nonlocality. The former concept can be understood as the possibilistic version of contextuality, while the latter refers to proofs of quantum probabilistic non-classicalities that are not based on violation of any noncontextuality (or Bell) inequality. The present work aims to build a bridge between these two concepts through what we call possibilistic paradoxes, which are sets of possibilistic conditions whose occurrence implies contextuality. As our main result, we demonstrate the existence of possibilistic paradoxes whose occurrence is a necessary and sufficient condition for logical contextuality in a very important class of scenarios. We discuss some consequences arising from the completeness of such possibilistic paradoxes. Finally, we review some inequality-free proofs under the light of the developed formalism.